STUDI ANALISIS MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DALAM MENGEMBANGKAN BERPIKIR KRITIS PESERTA DIDIK DI SMP NEGERI 1 PALU - Nina Arfiani (Scolae: Journal of Pedagogy, 2019)
This paper discusses "Study Analysis of Problem Based Learning Models in Developing Critical Thinking of Students in SMP Negeri 1 Palu" and the problems in this study are: How the effectiveness of problem-based learning models in developing students' critical thinking in PAI subjects in SMP N 1 Palu and what are the supporting factors and obstacles to the problem-based learning model in developing students' critical thinking in SMP N 1 Palu. This study uses a qualitative approach, data collection techniques through interview observation and documentation, data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate the effectiveness of problem-based learning models in developing critical thinking of participants in SMP Negeri 1 Palu has been well implemented. Problem solving in a learning process has an important role to create learning that is liked and liked by students and makes learning more meaningful so that students are able to develop their critical thinking. From the conclusion, the implication is that the learning model is something that is really needed by educators to achieve the goal, the school provides training to educators about the learning model, maintaining what has been done, and for students in SMP Negeri 1 Palu, regarding the ability to think critically through models educators use to always follow the learning cycle.